2017
DOI: 10.1200/jco.2017.35.15_suppl.e13537
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of safety and pharmacokinetics of NanoBB-1-Dox in patients with advanced solid tumors.

Abstract: e13537 Background: NanoBB-1-Dox is a novel drug candidate for systemic chemotherapy of glioblastoma multiforme (GBM). It is a nanoparticle-based formulation of doxorubicin, which enables passage of the drug across the blood-brain barrier and delivery to the tumor inside the brain. Preclinical studies demonstrated that NanoBB-1-Dox enabled considerable growth inhibition of an intracranially implanted 101.8 glioblastoma in rats and long-term remission in >20% animals, whereas the conventional doxorubicin for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…They are FDA-approved and have a slower degradation rate than PBCA, allowing for a more sustained delivery [148,149]. Furthermore, a formulation of PLGA nanoparticles loaded with doxorubicin (NanoBB-1-Dox) has been investigated in a phase-I clinical trial for the treatment of glioblastoma multiforme through systemic chemotherapy [150]. Following the good tolerance of the treatment, NanoBB-1-Dox will be investigated in a phase-II study, which might prove the ability of PLGA nanoparticles to cross the BBB in humans.…”
Section: Nanoparticles For Drug Delivery Through the Bbb Polymeric Namentioning
confidence: 99%
“…They are FDA-approved and have a slower degradation rate than PBCA, allowing for a more sustained delivery [148,149]. Furthermore, a formulation of PLGA nanoparticles loaded with doxorubicin (NanoBB-1-Dox) has been investigated in a phase-I clinical trial for the treatment of glioblastoma multiforme through systemic chemotherapy [150]. Following the good tolerance of the treatment, NanoBB-1-Dox will be investigated in a phase-II study, which might prove the ability of PLGA nanoparticles to cross the BBB in humans.…”
Section: Nanoparticles For Drug Delivery Through the Bbb Polymeric Namentioning
confidence: 99%
“…On the one hand, many PK studies have been carried out in nanomedicine and were analyzed by conventional means (55)(56)(57)(58)(59). A common method is non-linear mixed effects (NLME) modeling describing non-linear relationships using a limited number of population parameters and parameter variability.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…[2,3] On the contrary, most polymer nanoparticles disappear from the blood plasma more rapidly. Still, through a variety of species and disease models, [4][5][6][7][8][9] they led to surprising outcomes and improved the efficacy of drugs significantly. [4][5][6][7][8] Polymer nanoparticles composed of PLG, for instance, were successfully used in the formulation of doxorubicin [10][11][12] and other anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The investigational drug product NanoCore-7.4 has been developed for the treatment of glioblastoma multiforme. [4,9,10,16,17] It comprises doxorubicin that is clinically applied in the treatment of solid tumors and hematological malignancies. [18] Blood partitioning studies indicated the binding of >40% of the total dose of this PLG nanoparticle formulation to the cellular fraction of the blood.…”
Section: Introductionmentioning
confidence: 99%